Addressing environmental awareness through immersive VR experiences, gamification and hypothetical scenario development. Issue 2 (1st October 2021) - Esmaeili, Human; Thwaites, Harold
This research article presents part of a series of VR experiences that are focusing on persisting and globally recognized environmental issues. The main objective of this project is to visualize and address the situation through a different window compared to traditional awareness programmes. Although increased consciousness about environmental issues has been widely achieved through various forms of media, the sense of being confronted with the 'situation' may have not been created yet. This means that traditional awareness programmes can visualize the environmental impacts of unsustainable human activities but may not be able to fabricate scenarios in which individuals can face relevant consequences. Encountering undesired environmental impacts such as glacier meltdown, sea level rise, or landfill crisis, are not part of the daily routine of urban inhabitants living in artificially harnessed lands. This was the main notion for this research project. The initial idea was to create inhabitable lands that are severely damaged by human activities furnished with elements such as deforestation, deceased animals, water pollution, etc. However, this idea seems to be slightly raw and non-constructive. Therefore, in the second approach, multiple hypothetical scenarios, including an actual, were developed to gradually lead the users to the destinations created by themselves. For the first milestone of this project a recycling VR game targeting the majority of age groups, while still containing dark and bright elements without leaving undesired memories, was developed. The game was first presented during Malaysia's biggest United Nations concert/event Rock the Goals held on 25 September 2019 in Sunway University. The results from the pilot study and the data collected through user experience opened few windows for discussing possibilities of addressing environmental issues through VR. This article partly focuses on confrontation with undesired environmental impacts in full immersive VR experiences. The main discussion is centred around the effectiveness or ineffectiveness of various scenarios among different target audiences. Should we create virtual phobia from the environmental issues? Or must we focus on constructive educational experiences? Or a combination of both?